Structure and properties of Fe-B-C powders alloyed with Cr, V, Mo or Nb for plasma-sprayed coatings - Sukhova, O.V. (Вопросы атомной науки и техники, 2020)
In the present study, the microstructure development and properties of the starting Fe-B-C powders for plasma spraying fabricated by dispersing a consumable rotating rod were investigated as functions of alloying elements additions. These powders were prepared in the following compositional ranges: B (10…14 wt.%), C (0.01…0.5 wt.%), Me (0…5.0 wt.%), where Me – Cr, V, Mo or Nb, balance Fe. Structural properties were characterized by metallography, X-ray diffraction, scanning electron microscopy, and energy dispersive spectroscopy. Mechanical properties of the powders were measured by a Vickers indenter. Compression strength, oxidation resistance, and melting temperature were also determined. Chromium or vanadium were found to dissolve completely in Fe₂(B, C) and Fe(B, C) constituent phases of the Fe-B-C powders replacing iron and forming substitutional solid solutions. By entering into the iron borides structure, these alloying elements improve ductility and oxidation resistance but lower melting temperature and hardness of the powders. Molybdenum or niobium were mainly found in secondary phases such as Mo₂B, Mo₂(B, C) or NbB₂ at the Fe₂(B, C) boundaries. As a result, these alloying elements enhance hardness, oxidation resistance and melting temperature of the powders. Досліджували вплив легуючих елементів на процеси формування структури та властивостей порошків для плазмового напилення, виготовлених методом розпилення обертового стрижня. Склад порошків знаходився в наступному концентраційному діапазоні: B (10…14 ваг.%), C (0,01…0,5 ваг.%), Me (0…5,0 ваг.%), де Me – Cr, V, Mo або Nb, Fe – залишок. Структуру порошків вивчали методами металографії, рентгеноструктурного аналізу, сканувальної електронної мікроскопії, рентгеноспектрального мікроаналізу. Механічні властивості порошків вимірювали на мікротвердомірі Віккерса. Також визначали міцність на стиск, окалиностійкість, температуру плавлення. Хром та ванадій повністю розчиняються в структурних складових Fe₂(B, C) і Fe(B, C) порошків Fe-B-C, заміщуючи залізо в кристалічних ґратках фаз і формуючи тверді розчини заміщення. Проникаючи в структуру боридів заліза, ці елементи підвищують їх пластичність і опір окисленню, але знижують температуру плавлення і твердість порошків. Молібден та ніобій в основному присутні в структурі у вигляді вторинних фаз, таких як Mo₂B, Mo₂(B, C) або NbB₂, що виділяються по межах кристалів Fe₂(B, C). Як наслідок, ці легуючі елементи підвищують твердість, опір окисленню і температуру плавлення порошків. Исследовали влияние легирующих элементов на процессы формирования структуры и свойств порошков для плазменного напыления, изготовленных методом распыления вращающегося стержня. Состав порошков находился в следующем концентрационном диапазоне: B (10…14 вес.%), C (0,01…0,5 вес.%), Me (0…5,0 вес.%), где Me – Cr, V, Mo или Nb, Fe – остаток. Структуру порошков изучали методами металлографии, рентгеноструктурного анализа, сканирующей электронной микроскопии, рентгеноспектрального микроанализа. Механические свойства порошков измеряли на микротвердомере Виккерса. Также определяли прочность на сжатие, окалиностойкость, температуру плавления. Хром и ванадий полностью растворяются в структурных составляющих Fe₂(B, C) и Fe(B, C) порошков Fe-B-C, замещая железо в кристаллических решетках фаз и формируя твердые растворы замещения. Присутствуя в структуре боридов железа, эти элементы повышают их пластичность и сопротивление окислению, но снижают температуру плавления и твердость порошков. Молибден и ниобий в основном присутствуют в структуре в виде вторичных фаз, таких как Mo₂B, Mo₂(B, C) или NbB₂, выделяющихся по границам кристаллов Fe₂(B, C). Как следствие, эти легирующие элементы повышают твердость, сопротивление окислению и температуру плавления порошков.